Survival and Functional Immune Reconstitution After Haploidentical Stem Cell Transplantation in Atm-Deficient Mice - Duecker, Ruth Pia; Gronau, Lucia; Baer, Patrick C.; Zielen, Stefan; Schubert, Ralf (Frontiers in Immunology, 2021)
Hematopoietic stem cell transplantation (HSCT) has been proposed as a promising therapeutic opportunity to improve immunity and prevent hematologic malignancies in Ataxia-telangiectasia (A-T). However, experience in the transplantation strategy for A-T patients is still scarce. The aim of this study was to investigate whether different approaches of HSCT are feasible in regard to graft versus host response and sufficient concerning functional immune reconstitution. Atm-deficient mice were treated with a clinically relevant non-myeloablative host-conditioning regimen and transplanted with CD90.2-depleted, green fluorescent protein (GFP)-expressing, and ataxia telangiectasia mutated (ATM)-competent bone marrow donor cells in a syngeneic, haploidentical or allogeneic setting. Like syngeneic HSCT, haploidentical HSCT, but not allogeneic HSCT extended the lifespan of Atm-deficient mice through the reduction of thymic tumors and normalized T-cell numbers. Donor-derived splenocytes isolated from transplanted Atm-deficient mice filled the gap of cell loss in the naïve T-cell population and raised CD4 cell functionality up to wild-type level. Interestingly, HSCT using heterozygous donor cells let to a significantly improved survival of Atm-deficient mice and increased CD4 cell numbers as well as CD4 cell functionality equivalent to HSCT using with wild-type donor cells. Our data provided evidence that haploidentical HSCT could be a feasible strategy for A-T, possibly even if the donor is heterozygous for ATM. However, this basic research cannot substitute any research in humans.